Synthesis and characterization of natural rubber‐based telechelic oligomers via olefin metathesis. Issue 8 (10th September 2020) - Hu, Guangwei; Lin, Shaohui; Zhao, Boxin; Pan, Qinmin
Abstract: Metathesis degradation and functionalization of natural rubber (NR) were conducted with 1‐hexene, 1‐octene, 1‐decene, 1‐dodecene, trans ‐stilbene, and 4, 4′‐dibromo‐ trans ‐stilbene as chain transfer agents (CTAs) in presence of Grubbs 2nd generation catalyst to generate NR‐based telechelic oligomers that had been a long‐lasting challenge due to the structure and compositions of NR with various impurities. Orthogonal experiments were applied and the effects of the CTA type, CTA concentration, catalyst concentration, reaction time, and reaction temperature on the formation of telechelic oligomers were studied, indicating that the catalyst concentration was the major factor influencing the number average molecular weights ( M n ) and polymer dispersity index (PDI) of telechelic oligomers. The structures of the oligomers were characterized using 1 H NMR, 13 C NMR, and MALDI‐TOF‐MS, which confirmed the formation of the designed terminal groups. The results showed that well‐defined telechelic oligomers with a M n of a few thousand and a PDI around 1.6 were obtained, with potential applications in binder, lubricant and many other fields. Abstract : Metathesis degradation and functionalization of natural rubber were conducted with asymmetric and symmetric olefins as chain transfer agents in presence of a Grubbs catalyst to generate various valuable natural rubber‐based telechelic oligomers, which also bring out a feasible life‐cycle route of natural/synthetic rubber resources.